Revisiting Alu of The Swamp Dwellers by Soyinka and Views by Beauvoir in The Second Sex: Unifying Humanity Versus Feminist Separatism - Uddin, Md. Abu Saleh Nizam (Indonesian Journal of English Language Studies (IJELS), 2022)
This paper concentrates on a comparative study between Alu of the drama The Swamp Dwellers by Soyinka and the Feminist views of Beauvoir in The Second Sex while the areas of the drama so far explored and discussed are native narrative, political views, decline through modernization, moral-spiritual standpoint, family bonding and human-nature tie. In the drama, if the vital role played by Alu is construed, she appears as a woman figure of infinite capaciousness with her duties, responsibilities, feelings, commitments, rights and privileges in family and society. Alu succeeds because her human-centric Yoruba tradition gives support to her family-centric biology and psychology. But contrary to Alu, Feminist views disseminated by Beauvoir in The Second Sex embark on the estrangement of women from family and humanity. Thus, the paper seeks to unearth how Alu of Yoruba tradition harmonizes and unifies humanity through her role in family and society while Feminism of Beauvoir opposes them and wishes women to be separated. In this qualitative research of thematic analysis method, Family Systems Theory and Religious Humanism Theory were applied. By recommending for women the re-introduction of traditional human-centric life in family and society, this research may contribute to women’s emancipation from misery.